ANALISIS PENERAPAN METODE SILABA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Yudi Budianti; Fitri Indri Wardhani (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research was motivated by the low initial reading ability of Indonesian elementary school students. This is because teachers still use conventional learning methods where learning is only centered on the teacher while students are not involved much or are not active in learning. In this condition, the syllabic method (silaba) becomes an alternative solution method, because the syllabic method involves interaction between students and teachers, so that there is no longer any learning that only dominates the teacher or only dominates smart students. This research also aims to review how the syllable method (sylaba) affects the beginning reading abilities of lower grade elementary school students. The method used for the review is systematic or Systematic Literature Review (SLR) by analyzing research results that have been published nationally relating to the syllable method (sylaba) on the initial reading ability of lower grade elementary school students for Indonesian language lessons, sample analysis are 15 journals that have been published in the last 10 years. The journal discusses the syllable method, based on the findings of the analysis of the syllable method (sylaba) which has a positive influence. From each article or journal that has been analyzed, there are differences, but overall this research shows the conclusion that the syllable method for beginning Indonesian reading skills in lower grade elementary school students has a significant influence on elementary school students' reading abilities.